The Knowledge and Attitude of Integrated Pest Management Farmers Field Schools Alumni toward the Use of Pesticides in Klaten, Central Java, Indonesia - Andriarti Kusumawardani; Edhi Martono; Y. Andi Trisyono; Nugroho Susetya Putra (Jurnal Perlindungan Tanaman Indonesia, 2019)
The field schools in Indonesia employ an extension alternative model that is considered appropriate to change the habits and behavior of farmers to make them IPM experts in their field. This study was conducted to understand the behavior (knowledge and attitude) of farmers who have joined field schools, i.e. Integrated Pest Management Farmers Field School (IPM-FFS) and Landscape Integrated Pest Management (Landscape IPM), toward the use of pesticides in Klaten, Central Java, Indonesia. The research used a survey method with purposively selected respondents comprising 55 farmers of the IPM alumni and 25 farmers of the Landscape IPM alumni. A descriptive analysis was conducted to analyze the farmers’ knowledge and attitude toward the use of pesticides. Mann-Whitney U-test analysis was performed using Statistical Product and Service Solution (SPSS) version 23, to compare the knowledge and attitude of farmers regarding the use of pesticides. The results showed that the knowledge of farmers of  the Landscape IPM alumni regarding the use of pesticides was higher than that of farmers of the IPM-FFS alumni. There was no difference in the behavior of farmers between the IPM-FFS alumni and the Landscape IPM alumni regarding their attitude toward the use of pesticides.